2020
DOI: 10.1039/c9ob02556a
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the atroposelectivity in the synthesis of axially chiral thiohydantoin derivatives

Abstract: A DFT study is carried out in order to elucidate the racemization and cyclization mechanism as well as the atroposelectivity during the synthesis of 2-thiohydantoins. Computational data shows that the racemization occurs after cyclization with the assistance of triethyl amine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The 2-thiohydantoin ring has been also incorporated into the structures of several natural products such as Enzalutamide, which has been FDA-approved as a drug for castration-resistant prostate cancer ( Figure 1 ) [ 25 , 26 , 27 ]. Based on the high therapeutical significance of the 2-thiohydantoin-based compounds, the synthesis of a novel class of substituted-2-thiohydantoins has attracted great attention in recent decades [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 2-thiohydantoin ring has been also incorporated into the structures of several natural products such as Enzalutamide, which has been FDA-approved as a drug for castration-resistant prostate cancer ( Figure 1 ) [ 25 , 26 , 27 ]. Based on the high therapeutical significance of the 2-thiohydantoin-based compounds, the synthesis of a novel class of substituted-2-thiohydantoins has attracted great attention in recent decades [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ( S )-5-methyl-3- o -trifluoromethylphenylthiohydantoin ( 7 ), on the other hand, yielded RM / SP / SM / RP 1.4:52.4:0:46.2 at first, and after recrystallization, the P isomers this time were obtained as a 54.2:45.8 ( SP / RP ) mixture (Figure b,b′). Apparently, racemization has taken place at C5 of 6 and 7 . When the RM isomer was resolved micropreparatively by HPLC on a chiral column and the collected isomer was reinjected into HPLC for analysis, it was found that it converted to SM to give a 59:41 mixture of RM and SM isomers.…”
Section: Resultsmentioning
confidence: 99%
“…Several facile and efficient synthetic approaches have been developed for the synthesis of 2-thiohydantoins which allowed different structural variations at different positions [43,[52][53][54].…”
Section: Resultsmentioning
confidence: 99%